From the war of streaming to the war of windows: OTT strategies of the majors with theatrical releases - Benito García, José María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective of this work is to present the market structure of the main platforms that operate in this market and their investments in content, as well as to detect the content dissemination strategies and movie premieres of four of the five currently existing "majors ” from Hollywood that have added their own OTT platforms to their media conglomerates: Warner with HBO Max and Discovery+; Disney with Disney+, Hulu and SPN+; Paramount with Paramount+ and Pluto TV; and Universal with Uni-versal+ and Peacok.